2010
DOI: 10.1177/1420326x10367315
|View full text |Cite
|
Sign up to set email alerts
|

Visual Landscape Analysis of Urban Open Spaces: A Case Study of the Coastline of Göcek Settlement, Muğla, Türkiye

Abstract: This article presents a visual analysis of the landscape characteristic of Göcek settlement, a Mediterranean coastal town affiliated to Muğla, located in the south-west of Turkey. The aim was to provide an identity for a contemporary coastal town by studying use of its public open spaces. The analysis had four parts: data collection, development of forms, fieldwork and finally evaluation and synthesis. In the fieldwork section of the study, the coastline, which is considered outstanding in terms of its tourism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…During these visits, the students conducted observation studies under the guidance of the study preparation instructions given to them at the beginning of the semester. In the preparation of the "study preparation instructions", Malkoç (2008), Kilicaslan et al (2008), Malkoc et al (2010), Malkoc True et al (2014), Malkoç True and Özkan (2014), Malkoç True and Sönmez Türel (2017) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…During these visits, the students conducted observation studies under the guidance of the study preparation instructions given to them at the beginning of the semester. In the preparation of the "study preparation instructions", Malkoç (2008), Kilicaslan et al (2008), Malkoc et al (2010), Malkoc True et al (2014), Malkoç True and Özkan (2014), Malkoç True and Sönmez Türel (2017) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…11 'Locality' is inherent in the local natural characteristics and cultural characteristics 12 and is the key to prove and maintain self and local identity in urban and rural landscape. Less relevant research considers the perspective of entire cities, whereas more studies address architecture and neighbourhood scales, focusing on local identity and the perception of a specific part of the city [13][14][15] that lacks a macro-geographical and environmental perspective. Although previous research has indicated the relationship between urbanization and local cultural homogeneity, 16 there is little discussion on the different stages of urbanization from a cultural perspective.…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, this sort of studies plays an important role in characterizing a region. 8 They address a sense of natural and cultural aspects of an area 9 and are associated with a change of landscape views, people's responses and area's appearance. 10,11…”
Section: Introductionmentioning
confidence: 99%